KUALITAS LINGKUNGAN PERMUKIMAN KAWASAN PECINAN KOTA SEMARANG - Yuliastuti, Nany; Khaerunnisa, Isti (Diponegoro University, 2011)
Chinatown is a component of the urban area which has many unique possibilities and store a wide variety issuesrelated to its area development and social culture. Chinatown in Semarang is one area that has a specialtreatment from the local government of Semarang where it has a high commercial and cultural value. The areahas some issues that are often experienced by urban settlements in the high building density that causes thedifficulty of procuring open space and green open spaces, some of the environmental infrastructure damage suchas potholes, clogged channels to rubbish strewn everywhere. The purpose of this study was to assess theenvironmental quality of settlements in the Chinatown area of Semarang. General approach used in this study isa quantitative approach. While the analytical techniques used in this research is descriptive statistics, withdescriptive techniques of quantitative, qualitative and descriptive descriptive and comparative analysis ofweighting as an analytical tool used to support the analysis. The results of this study is the quality ofneighborhoods in the city of Semarang's Chinatown area belong to the category of Medium with a value of 50 inunits of percent. This value is derived from the analysis of public facilities and infrastructure conditions of theenvironment area, the analysis of the physical quality of the built environment, and public awareness of theenvironmental analysis has been done before, where all of the analysis is at a Moderate category. This indicatesthat the need to increase the quality of neighborhoods Chinatown area, in anticipation of a decline inenvironmental quality. A good public awareness of the environment in which they live will be able to preventdegradation of Semarang's Chinatown neighborhood area can even improve the quality of the settlements in theregion.